Study of the effect of multiple conductions on threshold voltage in a MIS-HEMT from 450 K down to 200 K - Perina, Welder F.; Martino, Joao A.; Simoen, Eddy; Peralagu, Uthayasankaran; Collaert, Nadine; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this work, the effect of the multiple conductions of a GaN based Metal-Insulator-Semiconductor High Electron Mobility Transistor (MIS-HEMT) when operating in a temperature range from 200K to 450K are evaluated experimentally. From 200K till 350 K the transfer curve of the 600nm gate length device shows the Zero Temperature Coefficient (ZTC) point clearly. However, for temperatures over 350 K, the threshold voltage (VTH) shift towards higher gate voltage, which prevents the presence of ZTC bias point. This behavior is better explained through the transconductance (gm) curve where the HEMT and MOS conductions of the devices are being affected differently by temperature, resulting in a competition of effects that changes the behavior of the device in both, gmmax and VTH as a function of temperature.
Keywords: basic parameters; GaN; heterostructure; MISHEMT; temperature; threshold voltage